THE ROLE OF TRADITION AS A PART OF THE ORGANIZATIONAL CULTURE OF A HUMANITARIAN SCIENTIFIC INSTITUTION IN BUILDING ITS TIME PERSPECTIVE - A. E. Vorobieva (Концепт: философия, религия, культура, 2017)
The article presents a study of the scientific institution organizational culture as a part of the national research culture. The problem becomes more relevant in the context of the modern Russian science reforming. The specifics of organizational culture in connection with the organization's branch of activity are observed. Values of specific scientific organizations depend not only on the values of the world of science, but also on the values of national culture. Correlation between the specifics of the Russian scientific environment and the mentality of Russians has been noted. Also the importance of studying the organization's common past in order to build its future is emphasized. The results of the research carried out in 4 focus groups consisting of employees of various laboratories of the Institute of Psychology of RAS are analyzed. The format of a group interview was based on the concept of organizational culture of E. Shane. In general, the organizational culture of the modern Russian humanitarian scientific organization preserves elements inherited from the Soviet humanitarian research organization, marked by orientation to the past. Employees feel their affiliation with a scientific school; there is a directorship tradition with representative functions and a short distance power.